Knowledge, attitude and practice study on bio-medical waste management among interns in a tertiary care hospital in Kancheepuram, Tamil Nadu - P., Mohan Kumar (International Journal Of Community Medicine And Public Health, 2019)
Background: All the wastes which are generated by the hospital are collectively called as health care waste. The medical interns exposed to various health hazards while working in the hospital during their training period. The study was done with the aim to assess the knowledge and awareness regarding various aspects of biomedical waste management amongst interns in a tertiary care hospital, Kancheepuram, Tamil Nadu. Methods: This was a descriptive cross sectional study carried out among 94 interns who had cleared the final MBBS exams and 81 interns who participated in the study after giving informed consent. A pretested, self-administered questionnaire on knowledge and awareness of bio-medical waste management policy and practice were given to the interns. Statistical analysis was done using Microsoft Excel. Results: Around 63% interns knew the correct definition of biomedical waste. 24.6% interns were aware that authorization is required for biomedical waste management by Central Pollution Control board. Only 22.2% of the interns had undergone the training programme and 64.1% were keen to attend training program for biomedical waste management. 88.8% knew about sources of generation of BMW and 96% had knowledge of bio-hazard symbol. 72.5% had knowledge of segregation of waste but none had knowledge of correct colour coding. 91.3% said that record maintenance was essential for biomedical waste management. 96.2% agreed that BMW is teamwork. Conclusions: It is hour of need for rigorous training, IEC program for all the medical interns to make them aware of the various health hazards associated with biomedical waste products.